MAKNA SIMBOLIK TARI KENCAR-KENCAR DI KABUPATEN KARANGANYAR - Anggita Febriana Putri; Lesa Paranti (Gesture: Jurnal Seni Tari, 2023)
Kencar-kencar dance is a traditional creation dance from Karanganyar Regency. Kencar-kencar dance has meanings of life which are symbolized through movement, accompaniment, make-up, costume, and property. The purpose of this research is to find out and analyze the symbolic meaning of Kencar-kencar Dance in Karanganyar Regency. The method used in this research is a qualitative method with a semiotic approach. Research on the Symbolic Meaning of Kencar-kencar Dance in data collection techniques used through observation, interviews, and documentation. Data validation techniques use source triangulation, technical triangulation, and time triangulation. Data analysis using data reduction, data presentation and conclusion. The results of the study show that the meaning of the Kencar-kencar Dance is found in motion, accompaniment, make-up, costume, and property. Living in harmony with mutual respect, mutual love, mutual respect, namely tolerance for differences that exist between communities to create harmony and peace between the Karanganyar people. Kencar-kencar dance has the meaning of Karanganyar which is brightly lit at night. The symbolic meaning in the Kencar-kencar Dance gives the spirit of life to the people of Karanganyar Regency